Calcium affects glucoraphanin metabolism in broccoli sprouts under ZnSO4 stress. (1st January 2021) - Zhuang, Li; Xu, Kexin; Zhu, Yinglian; Wang, Fengwu; Xiao, Junxia; Guo, Liping
Highlights: Ca 2+ exerted a positive impact on glucoraphanin biosynthesis. CaCl2 enhanced the conversion rate of glucoraphanin to sulforaphane in broccoli sprouts. Verapamil exerted a negative effect on glucoraphanin hydrolysis to form sulforaphane. Abstract: CaCl2, Ca 2+ chelator (EGTA) and Ca 2+ channel blocker (verapamil) were used to investigate mechanism of glucoraphanin metabolism in broccoli sprouts under ZnSO4 stress. CaCl2 treatment promoted sprout growth, reduced MDA (malonaldehyde) content and electrolyte leakage in sprouts under ZnSO4 stress. The highest MDA content and electrolyte leakage were obtained in ZnSO4 plus verapamil-treated sprouts. In addition, ZnSO4 plus CaCl2 treatment significantly enhanced glucoraphanin content and sulforaphane formation, while an opposite result was observed after ZnSO4 plus EGTA treatment; which were further supported by expression of glucoraphanin biosynthetic and hydrolytic genes as well as myrosinase (MYR) and epithiospecifier protein (ESP) activities. These results indicated that exogenous and endogenous calcium promoted glucoraphanin biosynthesis and the conversion rate of glucoraphanin into sulforaphane. Verapamil treatment also stimulated glucoraphanin biosynthesis, but exerted an adverse influence on sulforaphane formation from the hydrolysis of glucoraphanin because of much higher ESP expression and ESP activity than ZnSO4 treatment.